Kidney Health Literacy in Biology Learning: Indicator Patterns, Gender Differences, and Learner Clusters in Papua, Indonesia - Nova Riama Lumban Raja; Mimin Nurjhani Kusumastuti; Yanti Hamdiyati (CV. Dharma Samakta Edukhatulistiwa, 2026)
Kidney health literacy among adolescents remains under-examined within specific biology topics, particularly in eastern Indonesia. This study investigated self-reported kidney health literacy in biology learning among 108 eleventh-grade students (43 males, 65 females) from two senior high school in Sentani, Jayapura Regency, Papua, Indonesia. The instrument was adapted from the attitude questionnaire component of the kidney health literacy instrument developed by Wahyuni and Subiantoro (2024), covering four indicators: accessing, understanding, appraising, and applying kidney health information. Results showed that students were predominantly distributed across the Problematic (46.3%) and Sufficient (45.4%) categories. A one-sample t-test indicates that the population mean index did not differ significantly from the upper boundary of the Problematic category (M = 33.20, SD = 4.98; p = .680). Appraising was the weakest and most variable indicator (M = 30.86, SD = 7.58), while applying was the strongest (M = 34.95). No significant gender differences emerged from the Chi-Square, Fisher’s Exact,, and Independent Samples T-Tests, although female students showed greater score variability (SD = 5.74 vs. 3.61). K-Means cluster analysis identified three learner profiles: Proficient (23.1%), Underdeveloped (40.7%), and Transitional (36.1%). Appraising produced the highest F-value (F = 169.131), indicating that this indicator contributed most strongly to between-cluster differentiation. These findings suggest that appraising represents the most critical gap in students’ kidney health literacy and should be an explicit instructional target in biology learning on the human excretory system.